Komunikasi Kelompok dalam Edukasi Agama Islam Melalui Grup WhatsApp di RA Mutiara Hati - Santi Wulida Sahri Rahmadhani; Monika Teguh (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Religion serves as a guide for humans in their relationship with God, determining behavior according to His rules. Islam encourages parents to introduce religion from an early age. Schools, such as RA Mutiara Hati Surabaya, adapt technology by using WhatsApp for religious education. This research aims to understand group communication in Islamic education at RA Mutiara Hati through WhatsApp using adaptive structuration theory. The method involves quasi-qualitative research with interactive data analysis and data collection through interviews. The results show that communication through WhatsApp groups is effective for teachers and parents in religious education. The research findings, based on discussions through adaptive structuration theory, indicate that the group communication process in Islamic education through WhatsApp can be an effective communication medium between teachers and parents. The convenience provided by WhatsApp features contributes to the success of education.